Pelaksanaan Gadai Tanah Pusaka di Sumatera Barat (Studi Kasus di Kanagarian Koto Berapak Kecamatan Bayang Kabupaten Pesisir Selatan) - Dian Lyonanda Putri; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Land is an important element of forming the state, in achieving the purpose of the stateneed for government intervention, but the cultural diversity of each region is one of the factorsinhibiting the application of national law. The strength of the legal validity of the customary oneseen in West Sumatra, here against the prevailing land affairs is largely due to the customary lawis the property of the inheritance, as well as the implementation of the pledge in the area. Thepurpose of this study was to determine the inheritance and pawn what is the reason people do notcarry out the return of the land in accordance lien national law.This type of research is the socio-juridical , this research is descriptive analytic. Theresearch location is in Kanagarian Koto Berapak districts Bayang Pesisir Selatan Regency, whilepopulation and the overall sample is be related to the problem in this research. The data sourceused , primary data , secondary data and data tertiary. Data collection techniques with interviewsand review of the literature.Results from this study is the first, process of implementing a pawn of high inheritance isknown to mamak kepala waris, penghulu suku, the village chief and walinagari as well as lowerinheritance difference lower inheritance is known by parents and other relatives (biological).Second, the reason of penghulu suku do not carry out return and redemption pawn by Pasal 7 UUNo. 56 Prp Tahun 1960 is because indigenous people are very uphold the customs that have beenhanded prior to the national law governing, customary law would still apply because theindigenous Minangkabau “tak lakang dek paneh, tak lapuak dek hujan”In conclusion, the implementation of the pawn inheritance in Minangkabau, either lowinheritance or high inheritance the process is equally to be known by government officialsnagari, unless pawn under the hand. And the return of land pawn Minangkabau society continueto perform in accordance with customary law. Suggestions writer, first , so that people do noteasily make a pladge, especially just for subsistence. Secondly, the provisions of Pasal 7 thatprocedure is difficult to accepted by the Minangkabau society, especially in Kanagarian KotoBerapak, therefore it is necessary to find a way to solve it, so the purpose of Pasal 7 UU No. 56Prp Tahun 1960 can be achieved.Keyword: Pawn – Inheritance - In Minangkabau